Plasma antenna-reactor composite catalyst and preparation method thereof
By connecting the gold nanoparticles with terpyridine iron ([Fe(bpy)3]2+) through HS-PEG-COOH, the Au-[Fe(bpy)3]2+ composite catalyst is formed, which solves the problems of insufficient light response and low catalytic efficiency of plasma photocatalysts in the solar spectrum range, and realizes efficient use of carriers in the water decomposition reaction, significantly improving the photocatalytic performance and stability.
Patent Information
- Application Number
- CN202411669240.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing plasma photocatalysts have insufficient light response and low catalytic efficiency in the solar spectrum range, and traditional research mainly focuses on one half reaction, and the other half is regarded as a side reaction, resulting in low carrier utilization efficiency.
Using a plasma antenna-reactor composite catalyst, the Au-[Fe(bpy)3]2+ composite catalyst is formed by connecting the gold nanoparticles with tetrapyridine iron ([Fe(bpy)3]2+) through the carbon molecular chain thiol-polyethylene glycol-carboxyl (HS-PEG-COOH), thereby achieving electric field-mediated resonance energy transfer and plasma "hot" flow transmission.
It has achieved good catalytic efficiency at both the reduced end and the oxidation end of the water decomposition reaction, effectively utilizes "hot" electrons and "hot" holes, improves the utilization rate of photogenerated carriers, and significantly improves the photocatalytic performance and stability.
Smart Images

Figure CN119771498A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a plasma antenna-reactor composite catalyst and a preparation method thereof. Background Art
[0002] At this stage, the efficient use of non-fossil fuel clean energy is the only way to achieve sustainable development in the future. Solar energy is one of the most abundant clean energy sources on the earth. Due to its wide distribution and stable existence, its utilization plays a key role in solving existing energy and environmental problems. Photocatalysis can not only effectively realize the conversion of light energy into chemical energy, but also stably obtain high value-added chemical products, which has attracted widespread attention from researchers. However, traditional semiconductor photocatalysts have weak light absorption ability due to their large band gap, which limits their performance in solar energy utilization efficiency. Therefore, the development of efficient photocatalytic technology is of vital importance to the utilization of light energy and the optimization of energy structure.
[0003] Developing photocatalyst systems that have both strong and wide light response within the solar spectrum and excellent catalytic efficiency is an important way to develop photocatalysis. In recent years, plasma photocatalysis has received widespread attention. Compared with traditional wide-bandgap semiconductor photocatalysts, nanoplasmonic catalysts can produce efficient light absorption in the visible light region by virtue of the characteristic localized surface plasmon resonance (LSPR) phenomenon, thereby making full use of sunlight. However, common plasma metals such as precious metals such as gold, silver, and copper usually lack highly active redox active sites. In addition, the photogenerated electrons and holes generated by non-radiative relaxation of plasma are easy to recombine quickly. The above reasons lead to severe limitations on the performance of plasma materials directly as photocatalysts. Therefore, the development of a new plasma photocatalyst that can exhibit a strong and wide light response within the solar spectrum and has excellent catalytic efficiency is an important direction in the field of photocatalysis.
[0004] The many photophysical and photochemical mechanisms induced by plasmon resonance provide an effective path for plasma photocatalysis, which uses the photophysical response related to the localized surface plasmon resonance (LSPR) effect of nanoplasmons to achieve light collection, energy conversion and chemical changes. Through the excitation of LSPR and the radiative or non-radiative relaxation of excited states, nanoplasmonic materials can produce a series of photophysical and chemical responses, such as local electromagnetic field effects, hot carrier effects, photothermal effects, etc. The research of Professor Xia Xinghua of Nanjing University and Professor Huang Baibiao of Shandong University and their team confirmed that such processes can provide a direct driving force in plasmonic photocatalysis (J.Am.Chem.Soc.2015,137,7365; Angew.Chem.Int.Ed.2008,47,7931–7933).
[0005] However, the efficiency and stability of the hot electron transfer process at the interface between plasmon metals and catalytic components need to be further improved; at the same time, most of the existing research and applications only focus on one of the half reactions, and the other half is regarded as a side reaction. For example, the oxidation side of the photocatalytic carbon dioxide reduction reaction is usually a hole sacrifice or the oxidation of water, so only photogenerated electrons are effectively utilized, and holes do not participate in the generation of target products (Angew. Chem. Int. Ed. 2022, 61, e202207222; Appl. Catal. B 2022, 316, 121679), which greatly reduces the utilization efficiency of plasma photogenerated carriers; in addition, the differentiation, quantification and modulation of plasma photocatalytic mechanisms are extremely challenging, which also creates difficulties for the selective regulation of plasma photocatalytic reaction conditions, paths and products. The above problems have greatly limited the mechanism research and industrial application of plasmon photocatalysis. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a plasma antenna-reactor composite catalyst and a preparation method thereof, and provides a plasmon metal-molecule (Au-[Fe(bpy)3] 2+ ) The composite catalytic system can be used as a high-efficiency photocatalyst with good light absorption and catalytic properties, solving the problem of limited efficiency and stability of photocatalysts in the prior art; the catalytic system has good catalytic efficiency at both the reduction and oxidation ends of the water decomposition reaction, achieving effective utilization of "hot" electrons and "hot" holes, and improving the utilization rate of photogenerated carriers; it provides ideas for optimizing different photophysical enhancement mechanisms of plasma photocatalysts and improving the utilization rate of "hot" carriers, which is convenient for promoting the mechanism research and industrial application of plasmon photocatalysis.
[0007] In order to solve the above technical problems, the present invention provides a method for preparing a plasma antenna-reactor composite catalyst, comprising the following steps:
[0008] The gold nanoparticle colloid was mixed with HS-PEG-COOH solution and [Fe(bpy)3] 2+ The solutions were mixed and stirred in the dark for 10-14 h to obtain Au-[Fe(bpy)3] 2+ Composite catalyst.
[0009] The present invention combines gold (Au) nanoparticles with terpyridine iron ([Fe(bpy)3] 2+ ) are connected by a carbon molecular chain thiol-polyethylene glycol-carboxyl (HS-PEG-COOH) to form Au-[Fe(bpy)3] 2+ Composite catalyst. This catalytic system can simultaneously maintain the electric field-mediated resonant energy transfer and plasma "hot" carrier transport process, promote the efficiency of plasma carrier migration, and realize the plasma enhanced photocatalytic process; at the same time, gold nanoparticles and [Fe(bpy)3] 2+ The difference in surface charge contributes to the separation and directional migration of plasma "hot" electrons and "hot" holes. Through the photoelectrocatalytic water splitting reaction, excellent plasma photocatalytic processes are achieved at both the reduction and oxidation ends of the catalytic system, achieving the effective utilization of "hot" electrons and "hot" holes, improving the utilization rate of photogenerated carriers, and proving the photochemical enhancement effect, which accounts for the main contribution. This method provides ideas for optimizing different photophysical enhancement mechanisms of plasma photocatalysts and improving the utilization rate of "hot" carriers, which is convenient for promoting the mechanism research and industrial application of plasmon photocatalysis.
[0010] Furthermore, the preparation method of the gold nanoparticle colloid comprises the following steps:
[0011] Mix and dissolve tetrachloroauric acid and sodium citrate in deionized water, and add a reducing agent under stirring to obtain a seed solution;
[0012] Polyvinyl pyrrolidone and tetrachloroauric acid are mixed and dissolved in water, and ascorbic acid and potassium iodide are added to obtain a growth solution;
[0013] The seed solution was added to the growth solution, and the reaction was stirred for 20-30 minutes to obtain gold nanoparticle colloid.
[0014] Furthermore, the reducing agent is sodium borohydride.
[0015] Furthermore, after the gold nanoparticle colloid is prepared, it is washed with deionized water and stored at 4° C. for later use.
[0016] Furthermore, the [Fe(bpy)3] 2+ The preparation method comprises the following steps:
[0017] Dissolve ferrous chloride in deionized water, add bispyribac ethanol solution, then add ammonium hexafluorophosphate aqueous solution dropwise, mix and stir for 20-40 minutes to obtain [Fe(bpy)3](PF6)2.
[0018] Furthermore, after the [Fe(bpy)3](PF6)2 is prepared, it is washed with ethanol and dried in a vacuum.
[0019] Furthermore, the solvent of the HS-PEG-COOH solution is water; the [Fe(bpy)3] 2+ The solvent of the solution is water and ethanol in a volume ratio of 1: (0.5-1.5).
[0020] The second aspect of the present invention provides a plasma antenna-reactor composite catalyst prepared by the preparation method described in the first aspect.
[0021] Furthermore, the gold nanoparticles in the composite catalyst and [Fe(bpy)3] 2+ Combined, and the outer layer is wrapped with a HS-PEG-COOH layer with a thickness of 2-3nm.
[0022] The third aspect of the present invention provides the use of the plasma antenna-reactor composite catalyst described in the second aspect as a nanocatalyst in the field of photocatalysis.
[0023] Beneficial effects of the present invention:
[0024] Au-[Fe(bpy)3] 2+ The composite catalyst can simultaneously maintain the electric field-mediated resonant energy transfer and the plasma "hot" carrier transport process, promote the efficiency of plasma carrier migration, and realize the plasma-enhanced photocatalytic process; under light conditions, the local enhanced electric field generated by the nanoplasmonic particles induces the resonant energy transfer to the catalytic components, and the hot carriers generated directly participate in the redox process. The two mechanisms synergistically promote the photocatalytic process. The collective synergistic gain of photocatalytic performance is achieved and used for photocatalytic water decomposition. Under the excitation of a 520nm LED with a light intensity of 1 sun, the photocurrent density reaches -120.92mA / cm at an overpotential of -1V. 2 , the total current density reaches -194.47mA / cm 2 The photoelectrocatalytic hydrogen evolution rate was as high as 5194.02 mmol g -1 h -1 , showing excellent catalytic activity and stability.
[0025] The method of the present invention provides a method for optimizing different photophysical enhancement mechanisms of plasma photocatalysts and improving the utilization rate of "hot" carriers, which is convenient for promoting the mechanism research and industrial application of plasmon photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 where a is Au-[Fe(bpy)3] 2+ TEM image of the catalyst, b is the STEM image and EDS mapping image, and c is the Au-[Fe(bpy)3] 2+ and the Raman spectra of the control group under 633 nm incident laser; d is the XPS spectra of Au 4f and Fe 2p and the fitting;
[0028] Figure 2 The Au-[Fe(bpy)3] 2+ UV-Vis absorption spectra of catalyst and control group;
[0029] Figure 3 a and b are Au-[Fe(bpy)3] 2+ Steady-state (a) and transient (b) fluorescence spectra of the catalyst and control group under 350 nm excitation;
[0030] Figure 4 a and b are Au-[Fe(bpy)3] 2+ XPS spectra and fitting curves of Au 4f (a) and Fe 2p (b) in the dark and under 550nm monochromatic light illumination;
[0031] Figure 5 The Au-[Fe(bpy)3] 2+ Raman spectra of the catalyst and control group under 785 nm laser excitation;
[0032] Figure 6 a and b are Au-[Fe(bpy)3] 2+ LSV (a) and Tafel (b) curves of the catalyst and control group in 0.05 M sulfuric acid solution in the dark and under light;
[0033] Figure 7a and b are Au-[Fe(bpy)3] 2+ The catalyst was in 0.05M sulfuric acid solution at 100mW / cm 2 Photoelectrochemical hydrogen production rate under irradiation of xenon lamp light source (a) and 550nm (b) light source, with a continuous applied bias of -0.8V (vsAg / AgCl);
[0034] Figure 8 a and b are Au-[Fe(bpy)3] 2+ LSV (a) and it (b) curves of the catalyst in sulfuric acid solution and in 0.1 M sodium hydroxide solution in the dark and under light;
[0035] Fig. 9 a and b are Au-[Fe(bpy)3] 2+ The catalyst was in 0.05 M sulfuric acid and under a -0.2 V bias and 100 mW / cm 2 XRD spectra (a) and TEM images (b) before and after 2 hours of reaction under xenon lamp light source. (c) and (d) are Au-[Fe(bpy)3] 2+ The catalyst was in 0.05 M sulfuric acid and under a -0.8 V bias and 100 mW / cm 2 In situ Raman spectra of different reaction stages under 633nm (c) and 785nm (d) laser irradiation. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] This embodiment relates to a method for preparing a plasma antenna-reactor composite catalyst, comprising the following steps:
[0039] a. Preparation of gold nanoparticle colloid:
[0040] Aqueous solutions of tetrachloroauric acid (5 mM, 1 mL) and sodium citrate (1 mL, 5 mM) were mixed, 18 mL of deionized water was added, and sodium borohydride reducing agent (600 μL, 0.1 M) was added under vigorous stirring to obtain a seed solution. After the reducing agent was added, the color of the seed solution turned into dark brown.
[0041] Polyvinyl pyrrolidone (1 wt%, 1.25 mL) and tetrachloroauric acid (0.25 M, 300 μL) aqueous solution were mixed, and then a mixed solution of 1.25 mL of ascorbic acid (0.1 M) and 1.25 mL of potassium iodide (0.2 M) was added to obtain a growth solution.
[0042] 30 μL of the seed solution was added to the growth solution, stirred vigorously for 20 minutes, and then washed with deionized water three times to obtain a gold nanoparticle colloid, wherein the average particle size of the gold nanoparticles was 60 nm, and stored at 4° C. for future use.
[0043] b. [Fe(bpy)3] 2+ Preparation:
[0044] Ferrous chloride (0.80mmol, 0.1g) was dissolved in 1mL deionized water, and a solution of bipyridyl (2.56mmol, 0.4g) was prepared in 3mL ethanol. The two solutions were stirred and mixed, and then 2mL of ammonium hexafluorophosphate aqueous solution (1.8mmol, 0.29g) was added dropwise, and the mixed solution was stirred for 30 minutes to obtain a dark red precipitate of [Fe(bpy)3](PF6)2. Then, the precipitate was washed with ethanol three times and dried in a vacuum.
[0045] c. Au-[Fe(bpy)3] 2+ Preparation of catalyst:
[0046] The synthesized gold colloid (0.3 mL) was thoroughly washed three times with deionized water to remove the polyvinyl pyrrolidone on the particle surface. Then, 1 mL of HS-PEG-COOH (mW = 456) aqueous solution (1 mg / mL) and 150 μL of [Fe(bpy)3] 2+ The solution (water to ethanol ratio of 1:1, 4.6 mg / mL) was stirred for 12 h in the dark, washed twice with deionized water, and the volume was fixed to 1 mL to obtain Au-[Fe(bpy)3] 2+ According to the ICP-OES test results, Au-[Fe(bpy)3] 2+ The concentrations of gold and iron in the catalyst are 38.19±8.57ppm and 12.56±2.10ppm, respectively.
[0047] Test Case
[0048] 1. Au-[Fe(bpy)3] 2+ Catalyst structure characterization
[0049] The Au-[Fe(bpy)3] prepared in Example 1 2+ The catalyst was analyzed by transmission electron microscopy. Figure 1As shown in a, the transmission electron microscopy photo shows that there is an obvious HS-PEG-COOH layer of about 2.5nm thickness around the gold nanoparticles, which is the unfolded chain length of HS-PEG-COOH. The Au and Fe elements of a single catalyst particle were scanned using energy dispersive X-ray spectroscopy (EDS), and the results showed that Fe was distributed around the gold nanoparticles ( Figure 1 b). In addition, Au-[Fe(bpy)3] 2+ The Raman spectrum of [Fe(bpy)3](PF6)2 (1322, 1492, 1608 cm -1 etc.) and gold nanoparticles (1448 cm -1 , corresponding to the characteristic peak of PVP molecules on the surface of gold nanoparticles. -1 (Au) and 1492cm -1 ([Fe(bpy)3] 2+ ) shows the overlapping distribution of the two substances ( Figure 1 c). In addition, Au-[Fe(bpy)3] 2+ X-ray photoelectron spectroscopy (XPS) shows that the gold particles are in the metallic state. 0 Au formed by chemical bonding between the surface and the thiol groups 1+ The peak of Fe 2+ The corresponding characteristic peaks ( Figure 1 d), further demonstrated that gold nanoparticles and [Fe(bpy)3] 2+ The above results confirm that Au-[Fe(bpy)3] 2+ Successful formation of nanocomposites.
[0050] 2. Au-[Fe(bpy)3] 2+ Characterization of Catalyst Optical Properties
[0051] The Au-[Fe(bpy)3] prepared in Example 1 2+ The catalyst was tested for UV-vis absorption, and the results showed that Au-[Fe(bpy)3] 2+ The absorbance increased significantly ( Figure 2 ). Au-[Fe(bpy)3] 2+ The absorbance in the range of 450-550nm exceeds that of Au colloid and [Fe(bpy)3] 2+ The absorbance of Au-[Fe(bpy)3] 2+ After subtracting the absorbance of Au colloid from the absorbance of [Fe(bpy)3] 2+This phenomenon demonstrates the enhancement of absorbance via plasmon-mediated energy transfer.
[0052] In addition, under the excitation of 350nm light source, Au-[Fe(bpy)3] 2+ The fluorescence intensity of [Fe(bpy)3] 2+ Solution and a control group of physical mixture of the two ( Figure 3 a). At the same time, Au-[Fe(bpy)3] 2+ The fluorescence lifetime is longer than that of the control sample ( Figure 3 b), indicating a slower decay rate. The decrease in fluorescence intensity and the extension of lifetime indicate that the plasma carriers are 2+ Effective separation and transfer in.
[0053] Under the resonant excitation wavelength of 550nm, Au-[Fe(bpy)3] 2+ The Au 4f peak of the nanocatalyst has a significantly higher binding energy than that in the dark ( Figure 4 a); while the Fe 2p peak shifts to lower binding energy ( Figure 4 b), the shift indicates that the charge carriers generated by the gold nanoparticles under plasmon resonance are transferred to [Fe(bpy)3] 2+ In addition, in the Raman test, [Fe(bpy)3] 2+ Compared with the solution, Au-[Fe(bpy)3] 2+ [Fe(bpy)3] 2+ The characteristic peak of Figure 5 ). This result indicates that the Au nanoantennas 2+ The injection of charge lengthens the Fe-N bond and reduces its stretching frequency, which further proves that Au-[Fe(bpy)3] 2+ From Au to [Fe(bpy)3] 2+ Charge transfer pathways in molecules.
[0054] 3. Au-[Fe(bpy)3] 2+ Characterization of photocatalytic performance of catalysts
[0055] Au-[Fe(bpy)3] 2+ The resonant plasmon energy transfer and charge transfer mechanism may provide good photoelectrochemical potential and plasmonic photocatalytic performance. 2+There are lone pairs of electrons in the molecule, which have the potential to promote the reduction and oxidation processes and are expected to catalyze the complete decomposition of water. Under this premise, the two half reactions of hydrogen evolution and oxygen evolution are used to provide the reduction and oxidation environments respectively to explore their catalytic performance.
[0056] Au-[Fe(bpy)3] prepared in Example 1 2+ The catalytic performance of the plasmonic composite photocatalyst was first characterized in 0.05 M sulfuric acid. Combined with the linear sweep voltammetry (LSV) measurement results ( Figure 6 a), Au-[Fe(bpy)3] 2+ Shows high current density (-194.47mA / cm 2 ), lower starting potential (-0.4Vvs Ag / AgCl) and strong light response. The photocurrent density of the material is obtained by subtracting the current density under light from the current density under dark conditions to measure its photocatalytic activity. 2 ), irradiated with a 520nm light emitting diode (LED) can get -120.92mA / cm 2 The photocurrent density of 100 nm was obtained, which corresponds to the LSPR excitation wavelength of gold nanoparticles. Full-spectrum xenon lamp irradiation can also induce a significant photoelectrochemical response, although the degree is lower than that of the resonant 550 nm monochromatic light due to the wavelength-specific LSPR excitation. Next, the Tafel plot of the material was constructed ( Figure 6 b) to reflect the photoelectrochemical kinetics. In the dark or under the same light conditions, Au-[Fe(bpy)3] 2+ The Tafel slope of Au-[Fe(bpy)3] 2+ The onset potential of Au-[Fe(bpy)3] 2+ The photocurrent of the catalyst is much higher, which is consistent with the LSV and Tafel slope results. The catalyst has excellent photoelectrocatalytic efficiency. When a stable bias of -0.8V is applied, the photocurrent of the catalyst is 100mW / cm 2 ), we can get 4160.40mmol g -1 h -1 The average hydrogen evolution rate ( Figure 7 a), especially when irradiated with a 550nm monochromatic light source corresponding to the red edge of the LSPR absorption band of the gold nanoantenna, the average hydrogen evolution rate reached 5194.02mmol g -1 h -1 ( Figure 7 b). In order to further understand Au-[Fe(bpy)3]2+ The photocatalytic performance and mechanism of the plasma composite photocatalyst in the two half reactions of water splitting were investigated. The oxygen evolution ability of the material was tested in 0.1 M sodium hydroxide electrolyte. The results showed that Au-[Fe(bpy)3] 2+ Can maintain excellent and stable photocatalytic oxygen evolution process ( Figure 8 ).
[0057] In order to further confirm the stability of the catalyst, ICP-OES was used to quantitatively analyze the ratio of gold and iron elements before and after the hydrogen evolution reaction of the nanocatalyst. The value changed from 3.51 before the reaction to 3.83, which was only slightly decreased, indicating that [Fe(bpy)3] 2+ During the catalytic process, Au-[Fe(bpy)3] 2+ The XRD patterns and TEM images of the catalyst before and after the reaction show ( Fig. 9 a, b), with almost no structural or compositional changes. In particular, in the transmission electron microscopy images of the nanocatalyst after reaction, the HS-PEG-COOH layer was still observed around the gold nanoparticles, indicating the structural and morphological integrity of the nanocatalyst. In addition, under the same conditions as the photoelectrocatalytic test, the vibrational characteristic peaks of the in situ Raman spectrum of the nanocatalyst showed almost no change within 5 hours ( Fig. 9 c, d). These characterizations together prove that the Au-[Fe(bpy)3] 2+ The catalyst was remarkably stable during long-term catalytic testing.
[0058] In summary, the Au-[Fe(bpy)3] prepared by the method of the present invention 2+ The composite catalyst can simultaneously maintain the electric field-mediated resonant energy transfer and the plasma "hot" carrier transport process, promote the efficiency of plasma carrier migration, and realize the plasma-enhanced photocatalytic process; under light conditions, the local enhanced electric field generated by the nanoplasmonic particles induces the resonant energy transfer to the catalytic components, and the hot carriers generated directly participate in the redox process. The two mechanisms synergistically promote the photocatalytic process. A collective synergistic gain in photocatalytic performance is achieved and used for photocatalytic water decomposition.
[0059] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a plasma antenna-reactor composite catalyst, characterized in that: The steps include: The gold nanoparticle colloid was mixed with HS-PEG-COOH solution and [Fe(bpy)3] 2+ The solutions were mixed and stirred in the dark for 10-14 h to obtain Au-[Fe(bpy)3] 2+ Composite catalyst.
2. The method for preparing the plasma antenna-reactor composite catalyst according to claim 1, characterized in that: The preparation method of the gold nanoparticle colloid comprises the following steps: Mix and dissolve tetrachloroauric acid and sodium citrate in deionized water, and add a reducing agent under stirring to obtain a seed solution; Polyvinyl pyrrolidone and tetrachloroauric acid are mixed and dissolved in water, and ascorbic acid and potassium iodide are added to obtain a growth solution; The seed solution was added to the growth solution, and the reaction was stirred for 20-30 minutes to obtain gold nanoparticle colloid.
3. The method for preparing the plasma antenna-reactor composite catalyst according to claim 2, characterized in that: The reducing agent is sodium borohydride.
4. The method for preparing the plasma antenna-reactor composite catalyst according to claim 2, characterized in that: After the gold nanoparticle colloid is prepared, it is washed with deionized water and stored at 4° C. for later use.
5. The method for preparing the plasma antenna-reactor composite catalyst according to claim 1, characterized in that: The [Fe(bpy)3] 2+ The preparation method comprises the following steps: Dissolve ferrous chloride in deionized water, add bispyribac ethanol solution, then add ammonium hexafluorophosphate aqueous solution dropwise, mix and stir for 20-40 minutes to obtain [Fe(bpy)3](PF6)2.
6. The method for preparing the plasma antenna-reactor composite catalyst according to claim 5, characterized in that: After the [Fe(bpy)3](PF6)2 is prepared, it is washed with ethanol and dried in a vacuum.
7. The method for preparing the plasma antenna-reactor composite catalyst according to claim 1, characterized in that: The solvent of the HS-PEG-COOH solution is water; the [Fe(bpy)3] 2+ The solvent of the solution is water and ethanol in a volume ratio of 1: (0.5-1.5).
8. A plasma antenna-reactor composite catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. The plasma antenna-reactor composite catalyst according to claim 8, characterized in that: The gold nanoparticles in the composite catalyst are combined with [Fe(bpy)3] 2+ Combined, and the outer layer is wrapped with a HS-PEG-COOH layer with a thickness of 2-3nm.
10. Use of the plasma antenna-reactor composite catalyst according to claim 9 as a nanocatalyst in the field of photocatalysis.
Citation Information
Patent Citations
Polymerization catalyst for polythiourethane optical material, polymerizable composition containing the catalyst, polythiourethane resin obtained from the composition, and method for producing the res
CN101511895A
Covalently-bonded solid photocatalytic precursor material with broad-spectrum coordination function and application thereof
CN102532425A
Method for separating and recovering iridium salt catalysts for catalyzing light-controlled atom transfer radical polymerization (ATRP)
CN107915790A
Preparation method of Au / Cu5FeS4 / g-C3N4 plasma composite photocatalyst
CN111408396A
Solid phase photocatalyst and its preparing method
CN1470329A
Cited By
Layered manganese dioxide coated gold nanoparticle photocatalyst and preparation method thereof
CN122076435A